Pelatihan Pemanfaatan Limbah Stryrofoam Sebagai Media Tanaman Hidroponik Sistem Wick - Mu'ah Mu'ah; Masram Masram; Mesra Surya Ariefin; Roudlotul Badi'ah; Aranta Prista Dilasari (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to improve the skills of community members regarding wick system hydroponic vegetable planting using Styrofoam waste on limited land to improve the economy in Tumenggungan Village, Lamongan Regency. The method for implementing this service uses training consisting of counseling and mentoring. The evaluation instrument for this activity uses direct observation, which is then analyzed descriptively and based on the achievement of harvest results. The results of the service showed that there was a positive response from the training participants, which was demonstrated by the enthusiasm of the participants' activeness and interaction, starting from the presentation of the material, the practice of making hydroponics, planting hydroponics, until the completion of hydroponic harvesting. Apart from that, the hydroponic vegetable crops produced, namely kale, pak choy, and red spinach, can be used to meet daily consumption needs and open up opportunities to increase income in the family and the economy of the community in Tumenggungan Village, Lamongan Regency.